Corporate governance in the US and global settings - Ferris, Stephen P.; John, Kose; Makhija, Anil K. (Advances in financial economics, 2014)
Volume 17 of Advances in financial economics, entitled "Corporate governance in the US and global settings" will provide further insights into corporate governance in the US & global economic and financial environment by publishing international, within-country and cross-country comparative studies. The volume will be edited by the series editors, Kose John, New York University, Anil Makhija, Ohio State University, and Stephen P. Ferris, University of Missouri.